Calbindin D-28k and parvalbumin immunoreactivity in the frontal cortex in patients with frontal lobe dementia of non-Alzheimer type associated with amyotrophic lateral sclerosis. Issue 3 (March 1993) - Ferrer, I; Tuñón, T; Serrano, M T; Casas, R; Alcántara, S; Zújar, M J; Rivera, R M
Abstract : The morphology and distribution of local-circuit neurons (interneurons) were examined, by calbindin D-28k and parvalbumin immunocytochemistry, in the frontal cortex (area 8) in two patients with frontal lobe dementia of non-Alzheimer type associated with classical amyotrophic lateral sclerosis (ALS), and in seven normal cases. The density of calbindin D-28k immunoreactive cells was dramatically reduced in ALS patients, but the density of parvalbumin-immunoreactive neurons was preserved. Decreased density of calbindin D-28k-immunoreactive neurons, which are mainly located in the upper cortical layers, may interfere with the normal processing of cortico-cortical connections, whereas integrity of parvalbumin-immunoreactive cells may be associated with the preservation of the major inhibitory intracortical circuits in patients with frontal lobe dementia.